Ultrafast dynamics in rubrene and its spectroscopic manifestation - Hu, Wangjun (2020)
A multimode Brownian oscillator model is employed to investigate absorption line shapes of rubrene in solutions and thin films. Excellent agreement has been obtained between simulated and measured absorption spectra. Furthermore, using the parameters obtained from the fitting absorption spectra of rubrene, the dynamics of singlet fission is explored by the Dirac–Frenkel time-dependent variation with multiple Davydov trial states. By comparing the absorption spectra between a conical intersection model and the multimode Brownian oscillator model, the optimal system–bath coupling parameter of η = 0.2 is determined, and ensuing population dynamics of the S1 state is found to concur with a previously proposed coherent singlet fission mechanism. We further simulate the two-dimensional spectra to reveal the wavepacket dynamics on both excited state and ground state potential energy surfaces. It is demonstrated that the wavepacket motion of tuning modes plays a significant role in the evolution of two-dimensional spectra.